Dampak Rasio Keuangan Terhadap Pertumbuhan Laba (Studi Kasus Perusahaan Manufaktur Sektor Industri Barang Konsumsi Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - yitda, gartika; Safitri, Maria (Jurnal Akuntansi & Keuangan Unja, 2024)
This study aims to analyze the positive and significant impact of Total Asset Turnover (TATO), Debt to Equity Ratio (DER), and Quick Ratio on earnings growth, focusing on case studies of manufacturing companies in the consumer goods industry sector, especially the food and beverage sub-sector, which are listed on the Indonesia Stock Exchange during the 2019-2023 period. The sample used in this study consisted of 25 companies. The data analyzed is secondary data, and the analysis method used is EViews (Econometric Views) software. EViews is a statistical software that is widely used in econometric and economic data analysis, thanks to its ability to handle complex economic models, as well as time series, cross-section, and panel data. The results showed that TATO, DER, and Quick Ratio did not have a significant influence on profit growth in the consumer goods industry sector. In addition, profit growth in this sector is influenced by independent variables by 83.877%, while the remaining 16.123% is influenced by other factors not included in this study.